Pengayaan Polifenol Total dari Daun Kadamba Menggunakan Metode Ekstraksi Berbantu Mikrowave Berbasis Pelarut Hijau: Total Polyphenols Enrichment from Mitragyna speciosa Korth Havil Leaves Using Green Solvent Based Microwave-assisted Extraction Method - Ahmad, Islamudin; Yusniah, Andi; Nur, Yuspian; Prabowo, Wisnu Cahyo; Herman (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
The present study aims to optimize the natural deep eutectic solvent (NADES) as a green solvent-based microwave-assisted extraction (MAE) of total polyphenols content (TPC) from Mitragyna speciosa Korth Havil leaves using response surface methodology (RSM). Preparation of natural deep eutectic solvent (NADES) as a green solvent was performed by melting the two-component of malic acid and glucose using a magnetic stirrer. The leaves sample was extracted using the NADES-MAE method with various extraction conditions with four factors and three levels (Box Behnken Design) and optimized using RSM with licensed software of Design Expert V12. TPC was determined using a Folin-Ciocalteau reagent and absorbance was measured on a UV-VIS spectrophotometer at 770 nm and gallic acid as a standard. This study was obtained the optimum extraction conditions include: NADES ratio (malic acid: glucose) of 1:2 g/g, 50% microwave power, a solvent-sampel ratio of 12:1 mL/g, and extraction time for 7 minutes. The optimum conditions were obtained according to the equation formula: TPC = 165.17 – 33.97X1 + 38.36X2 – 6.08X3 + 16.12X4 – 62.77X1X2 + 79.61X12X2, where a R2 value = 0.7102 with a TPC prediction of 402.087±43.81 mg GAE/g sample. These conditions can be used to extract TPC from this plant efficiently, quickly, easily, and environmentally friendly.